Effectiveness of financial incentives for control of viral hepatitis among substance users: a systematic review and meta-analysis - Wang, Wanchen; Zhang, Lu (Frontiers in Public Health, 2024)
BackgroundHepatitis B virus (HBV) poses a significant global health challenge in substance users who are at a higher risk of infection. Financial incentives have been proposed as a strategy to enhance vaccine uptake among high-risk groups. This meta-analysis aims to assess the effectiveness of financial incentives in increasing HBV vaccination rates among substance users.MethodsA literature search across various databases was done for randomized controlled trials (RCTs) and non-randomized trials evaluating the impact of financial incentives on HBV vaccination rates in substance users. Six studies with a total of 3,886 participants were included. The GRADE approach was used to assess the quality of evidence, and a random-effects meta-analysis was done to calculate pooled risk ratios (RRs) for vaccination uptake.ResultsFinancial incentives were associated with a significant increase in the HBV vaccination uptake rates among substance users, with pooled RR of 2.261 (95% CI: 1.327–3.851), despite considerable heterogeneity (I2 = 93.7%). Sensitivity analysis confirmed the robustness of these findings. However, GRADE assessment indicated a very low quality of evidence, primarily due to risk of bias, inconsistency, imprecision, and potential publication bias, highlighted by a significant Luis Furuya–Kanamori (LFK) index of 6.42.ConclusionFinancial incentives significantly improve HBV vaccination rates among substance users, underscoring their potential as a public health intervention in this high-risk population. Low quality of evidence calls for further high-quality RCTs to confirm these results and explore the most effective incentive strategies.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024505277, identifier CRD42024505277.